Note to Readers - Gilbert S. Suzawa, Ph.D. (Journal of Interdisciplinary Sciences)
Dear Readers, I was recently attracted to the Volume 2, Issue 1 (May 2018) digital issue of Journal of Interdisciplinary Science (JIS) via a reference to one of my articles in the domain of Education. What I found at the website was a new journal, rudimentary but nevertheless quite impressive—the beginning of an inter-continentally based academic journal accepting research and scholarly manuscripts from many disciplines for review and publication on a global basis. I am a strong advocate of multidisciplinary thinking. During my academic career spanning approximately sixty years, I have been interested in a number of disciplines. First, as an undergraduate student at the University of Hawaii, I had an interest in Eastern Religions and Western Philosophies. As a graduate student at the University, I studied Economic Development (Developing Countries) and was fortunate to interact with students from all over Asia who were selected to attend the East-West Center. Subsequently, I attended Brown University in Providence, Rhode Island to earn a Ph.D. in mathematical economics. During my teaching tenure at the University of Rhode Island, I became interested in exploring some topics in Education. Editor-in-Chief Mani Man Singh Rajbhandari and his editorial and support teams have done another note-worthy job of putting together Volume 2, Issue 2 of JIS in a timely fashion. The issue contains articles from such disciples as Education, Gender Study, Political Science, Psychology, Sociology, etc. In my opinion, this journal is destined to gain a wide influence in the niche of non-specialized academic journals. I encourage you to give JIS first priority when it comes to consideration of where to submit your completed manuscript. It is with great pleasure that I add my name to the list of Advisors to JIS and extend my gratitude to Editor-in-Chief — Dr. Rajbhandari and his staff for the completion of this issue.